Coactivator networks orchestrating noncanonical AR programs in enzalutamide-resistant CRPC - Gardner, Ephraim J.; Ponnusamy, Sasikumar; Adelaiye-Ogala, Remi (Frontiers in Oncology, 2026)
Resistance to androgen receptor (AR)-targeted therapies remains a major clinical challenge in the treatment of castration-resistant prostate cancer (CRPC). Emerging evidence suggests that Enzalutamide resistance is not solely due to the loss of AR dependency but can also arise from epigenomic reprogramming of the AR cistrome toward noncanonical gene networks. Recent studies have revealed that this reprogramming is mediated by previously unrecognized coactivators, including CXXC5, TET2, and EZH2, which cooperate with AR to establish a transcriptional landscape that supports lineage plasticity and therapeutic evasion. These noncanonical AR transcriptional programs enable CRPC cells to survive under continued AR blockade, acting as a transitional state towards neuroendocrine differentiation. Pharmacologic disruption of these coactivators abrogates noncanonical AR activity and suppresses tumor growth, highlighting a tractable vulnerability. These findings redefine AR signaling in advanced disease, suggesting that targeting noncanonical AR coactivators could offer a novel therapeutic paradigm to overcome resistance. Advances in single-cell and epigenomic profiling are poised to delineate further the heterogeneity and dynamics of AR cistrome remodeling in treatment-refractory prostate cancer.